Pancasila as an ontological foundation for digital ethics: Reaffirming humanistic values in Indonesia's exponential technological era - Ananda Marcella; Nurizzi Rifqi Ferdian (Journal of National Paradigm-Based Resilience Strategy, 2025)
Background: The rapid acceleration of global technological advancement has fundamentally altered societal structures, yet it simultaneously triggers an ontological crisis that threatens human dignity and social trust. Methods: This study employs a qualitative, normative-philosophical approach to critically analyze the intersection of digital ethics and humanistic values within the Indonesian context. It synthesizes existing legal frameworks, specifically the national data protection regulations, with core Pancasila principles to evaluate contemporary governance challenges. Findings: The findings demonstrate that technological progress without a human-centric moral compass risks becoming divisive; however, integrating Pancasila as an ontological foundation provides a robust ethical framework for digital governance. This integration bridges the gap between algorithmic efficiency and the protection of individual rights. Conclusions: It is concluded that reasserting Pancasila values is essential for navigating the complexities of the digital era, ensuring that technology serves to enhance rather than diminish social cohesion. Novelty/Originality of this articles: This paper offers a fresh perspective by explicitly contextualizing Pancasila as a functional, pragmatic foundation for digital ethics, moving beyond mere theoretical discourse toward actionable policy alignment in Indonesia’s technological landscape.